Semi-Arid Plantation by Anatolian Black Pine and Its Effects on Soil Erosion and Soil Properties - Sezgin Hacisalihoglu (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the effects of Anatolian Black pine [(Pinus nigra Arn. subsp. pallasiana (Lamb.) Holmboe] plantation on hydro-physical soil properties and soil loss were investigated. This study was carried out on the afforestation field of Anatolian Black Pine in the Gölbaşı district of Ankara province, which is included in the arid and semi-arid regions. Totally 48 soil sample in two soil depth level (0-20cm, 20-50cm) were collected from forest (36 soil sample) and barren (control) area (12 soil sample). Hydro-physically important soil properties were analysed [Sand (%), Silt (%), Clay (%), Organic Matter (%), pH, Field Capacity (%), Wilting Point (%), Saturation (%), Available Water Holding Capacity (cm/cm) Saturated Hydraulic Conductivity (cm/hr), Bulk Density (gr/cm3)]. And soil loss in a unit area by using ABAG (Allgemeine Boden Abtrags Gleichung) model was estimated. Soil properties and soil loss amount relations among the land use group were determined. Topsoil (0-20cm) and subsoil (20-50cm) properties except subsoil organic matter were significantly affected by land use group. Finally, Significant changes were found for annual soil loss amounts in a unit area. Avarage annual soil loss in planted area was found approximately 5.5 times less than barren area at 0-50 cm soil depth. Vegetation factor (C) which is one of the most important components of the soil loss equation, has been significantly affected by afforestation in a short period of 40 years and thus it was a variable to reduce to soil loss.